A CORPUS-BASED STUDY OF VERB INFLECTIONAL AFFIXATION IN ENGLISH: INSIGHTS FROM DAWN NEWSPAPER - Saba Nousheen; Ariha Ijaz; Afsheen Nadeem; Hajra Waseem (International Journal of Contemporary Issues in Social Sciences, 2024)
The current research investigates the patterns and usage of English verb inflectional affixes in the Dawn newspaper, an English-language daily in Pakistan. By using a corpus-based method, the study seeks to gain a thorough insight into verb inflectional affixation by examining a one-week newspaper article. The research utilizes the software AntConc to analyze verb inflectional affixes, specifically looking at tense, aspect, voice, and person-number agreement. The main objectives are to recognize and classify the verb inflectional affixes utilized, as well as to examine their frequency and distribution in the corpus. The research aims to discover particular language patterns and deviations specific to media in a non-native English setting through analysis of the dataset. It is anticipated that the results will improve the comprehension of English verb morphology in academic written materials, supplying important knowledge to the field of corpus linguistics. The present research also has practical applications for the teaching and learning of English, especially in environments where English is acquired as a second language. The findings could impact teaching strategies and enhance reading comprehension and writing abilities by matching instructional approaches with the known use of verb inflectional affixes in professional and academic environments. In a nutshell, the present research connects theoretical linguistic studies with practical educational uses, offering real-life proof of how English verb structures are used in Pakistani media.